Defensive behavior of the invasive alien hornet, Vespa velutina, against color, hair and auditory stimuli of potential aggressors - Moon Bo Choi; Eui Jeong Hong; Ohseok Kwon (PeerJ, 2021)
Background During recent years, invasion of the yellow-legged hornet (Vespa velutina) has occurred in Europe, Korea and Japan, and stinging accidents often occur as some V. velutina nests are in places where humans can reach them. Misleading information regarding precautionary measures for mitigating wasp attacks has only exacerbated the situation. In this study, we sought to identify appropriate countermeasures by analyzing wasp defensive behavior, with a focus on color, hair and auditory stimuli. Methods Defensive behavior was analyzed using video recordings by creating an experimental frame to attach experimental bundles to nine V. velutina nests in Daegu and Gyeongbuk, South Korea. For the color experiment, eight-color and single-color tests were conducted with bundles of eight colors (black, brown, yellow, green, orange, gray, red and white), and the difference in defensive behavior was tested between black hair/hairless and green hair/black hairless configurations. Results When presented simultaneously with bundles of eight different colors, V. velutina showed the greatest and the longest defensive behavior against the black bundle, followed by brown. A similar response was observed in single-color tests. Furthermore, there was no significant difference in the defensive behavior against black hair and black hairless, but the duration of defensive behavior was longer for black hair. A comparison between green hair and black hairless stimuli indicated that wasps are more sensitive to color than to hair texture. Vespa velutina showed no discernible responses when exposed to selected auditory stimuli (human conversation and loud music). Dark colors and dark hair are characteristic features of potential predators, to which wasps are evolutionarily predisposed, and are accordingly likely to provoke strong defensive responses. The results of this study provide scientifically credible information that can be used to base appropriate precautionary measures against wasp attacks.